Spinal Cord Injury Provider Knowledge and Attitudes Toward Bacteriuria Management and Antibiotic Stewardship. Issue 12 (13th May 2020) - Skelton, Felicia; May, Sarah; Grigoryan, Larissa; Poon, Ivy; Holmes, Sally Ann; Martin, Lindsey; Trautner, Barbara W.
Abstract : Introduction: Bacteriuria, either asymptomatic or urinary tract infection, is common in persons with spinal cord injury or disorder (SCI/D). In the Veterans Health Administration (VHA), conflicting clinical practice guidelines make appropriate bacteriuria management and antibiotic stewardship challenging. Objective: To explore SCI/D provider knowledge, attitudes, and teamwork around bacteriuria management during the VHA SCI/D annual examination. Design: Mixed methods. Setting: VHA SCI/D centers. Participants: SCI/D staff providers and physical medicine and rehabilitation resident physicians. Main Outcome Measurements: Knowledge, safety, and teamwork scores on bacteriuria management using a validated questionnaire. Themes on barriers and facilitators to bacteriuria management during the SCI/D annual exam, and attitudes toward antibiotic stewardship in general. Results: We received 84 responses from 344 distributed surveys, with a response rate of 24%. Thirty percent of all participants endorsed incorrect triggers for obtaining a urine culture (change in urine color, cloudiness, or odor). The type of organism identified on culture drove unnecessary antibiotic use; 57% would treat asymptomatic bacteriuria if caused by extended spectrum beta‐lactamase Escherichia coli . There were no significant differences between the median (interquartile range [IQR]) knowledge score of the staff providers (70.6 [58.8‐82.4]) and the resident physicians (64.7 [58.8‐82.4]), but the teamwork climate scores ( P = .02) and safety climate scores ( P < .01) were higher among staff providers than among resident physicians. Interview analysis identified how the limited recall of content among SCI/D providers of the guidelines for bacteriuria was a potential barrier to their use but attitudes toward guidelines and antibiotic stewardship initiatives were positive. Conclusion: All participants objectively demonstrated actionable gaps in bacteriuria management and expressed uncertainty in their knowledge during qualitative interviews. Through addressing these gaps, we can develop effective antibiotic stewardship programs for the VHA SCI/D system of care.